CRITICAL RACE THEORY AND FEMINIST LEGAL THEORY: PERSPECTIVES ON TRANSFORMATION OF THE JUDICIARY (The Pretoria Student Law Review, 2021)
Referring to judicial appointments, Plasket J commented in 2013 that he could see ‘no basis on which [the Judicial Service Commission] could refuse to appoint a suitably qualified person’ in the presence of qualified white candidates.1 He was not alone in this view. Others have suggested that the Judicial Service Commission (JSC) is biased in favour of black and female candidates to the detriment of their white male counterparts.2 In this article, I will not endeavour to determine whether this bias in fact exists. The aim of this article is to explore Feminist Legal Theory (FLT) and Critical Race Theory (CRT) perspectives on transformation and the right to equality, with particular attention paid to transformation of the judiciary. This article consists of six parts. In the first section, the historical context of the JSC’s establishment, as well as the standard against which its decisions are measured, is explored. Secondly, the right to equality viewed through the lens of transformative constitutionalism is assessed. The third and fourth segments of this article focus on FLT and CRT respectively. Fifthly, I analyse the commentary from CRT and FLT scholars on human rights and transformative constitutionalism. Finally, I attempt to justify the act of abstention from making appointments in relation to FLT and CRT’s notion of refusal.
Keywords: judicial appointments; Feminist Legal Theory; Critical Race Theory; transformation; right to equality